Effects of Moringa oleifera extract on inflammaging markers, muscle mass, and physical endurance in geriatric mice model - Budiningsih, Fatichati; Purwanto, Bambang; Wasita, Brian; Poncorini, Eti (Narra J, 2025)
A comprehensive approach to managing frailty is required due to the increasing number of elderly. Physical frailty, associated with inflammatory processes and a loss of muscle mass, can significantly impair health status. The aim of this study was to determine the effect of Moringa oleifera Lam. leaf extract on frailty in geriatric mice model. An experimental study was conducted using a post-test-only control group design using  Mus musculus Balb/C mice aged eight weeks. The animals were divided into five groups: negative control group received intraperitoneal injections of normal saline (0.5 cc/day) for eight weeks, positive control group received D-galactose (150 mg/kg body weight (BW)/day) only, and three treatment groups treated with 150 mg/kg of D-galactose intraperitoneally for eight weeks followed by 100 mg/kg BW, 200 mg/kg BW, and 400 mg/kg BW of M. oleifera leaf extract orally for five weeks. At the end of the study, the blood levels of malondialdehyde (MDA), transforming growth factor-beta (TGF-β) and caspase-3, as well as caspase-3 expression in skeletal muscle, skeletal muscle mass fibrosis, and physical endurance were measured. The results showed that a dose of 400 mg/kg/day of M. oleifera leaf extract had the most significant effect on lowering MDA, TGF-β, and caspase-3 expression in skeletal muscle tissue, skeletal muscle fibrosis, and improved physical endurance compared to other groups (p<0.001). This study highlights that M. oleifera leaf extract reduced frailty in geriatric mice model-induced using D-galactose by reducing inflammaging factors, thereby improving physical endurance.